Joseph Beuys : Incontro con Beuys. - de Domizio, Lucrezia; Durini, Buby; Tomassoni, Italo (Pescara : D.I.A.C. Editrice Pescara, 1984)
An ample register of Joseph Beuys' life and works and a complete and updated bibliography make this "incontro" both a vehicle of knowledge and a necessary working tool.
The protagonists of this book have an intense rapport among themselves, derived from an "incontro", from which each of them has drawn his own suggestions and specific ways of working. Born of this idea, the book proposes to illustrate this rapport and to document this "incontro", along an intensive scale of "stations", which develop like a novel from the theoretical ouverture to a high quotient of informative narration provided by the photos (all of them unpublished), from the diary pages to the critical commentary. Caught in the dynamic connection of the meaning that emerges from the text , the reader, witness-like, is involved in the facts and the ideas ; he will follow once more a route, which, having at its beginnings a broadened concept of creativity, is among the most fascinating and complex expressions of world art after 1945.
biog. p. 381-383
geselect. bibliog. p. 379-380
Duits
boek
Keywords: Beuys, Joseph